The Conflicting Soviet Responses to the Lausanne Process (1922-1924) - R. Matos Franco (Vestnik MGIMO-Universiteta)
The article examines the Soviet responses to the Lausanne Process, which took place from May to November 1923. The process involved the trial of Russian émigrés Moritz Conradi and Arkadii Polunin, who were accused of murdering Vatslav Vatslavovich Vorovskii, the Soviet representative in Italy and head of the delegation to the Lausanne Conference, on May 10, 1923. The acquittal of Conradi and Polunin by a Swiss jury on November 16, 1923, under the verdict of "not guilty," as they were seen as avenging victims of Soviet repression, had a significant impact on the Russian emigration. While the historiography increasingly recognizes the role of various Russian émigrés in turning the trial into a denunciation of Bolshevism, little is known about the Soviet government's response to Vorovskii's killing and the efforts of the People's Commissariat of Foreign Affairs (NKID) to participate in the legal proceedings. By analyzing unpublished letters written by Soviet government officials found in the Archive of Foreign Policy of the Russian Federation and considering the international context of 1923, this study aligns with the historiographic trend that emphasizes collective leadership and institutional autonomy in Soviet foreign policy decisions following Lenin's increasing isolation in late 1922. The research demonstrates that when the Swiss government prevented the Soviet counterpart from participating as a legal party in the process, Moscow resorted to non-traditional foreign projections, which encompassed actions beyond formal diplomacy, and even involved non-communist actors to present the USSR in a positive and "objective" light at Lausanne. However, the bureaucratic complexities of the Soviet state hindered success in court. Thus, the handling of the Lausanne Process by the prosecution serves as an illustrative example of how post-Civil War Soviet institutions operated in relation to one another, characterized by intricate dynamics and an entrenched bureaucracy, far from the alleged "totalitarian" tendencies.